Implementation of Self-Evaluation Exit Tickets in Self-Organized Learning Environments (SOLEs) in Online Learning - Nicky Dwi Puspaningtyas; Sugama Maskar; Putri Sukma Dewi; Yurizka Melia Sari (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2024)
Effectiveness is one of the main problems in the online learning process. This becomes a benchmark for success in achieving learning objectives. Therefore, educators must be careful in choosing creative and innovative strategies both in terms of learning strategies and assessment strategies. Like the Self-Evaluation Exit Ticket assessment strategy which offers various advantages for educators and students. This research aims to determine the effectiveness of applying the Self-Evaluation Exit Ticket technique as an assessment strategy in learning. The subjects in this research were eighteen Mathematics Education students at a private higher education institution in Indonesia who took Number Theory courses online. Where, the material that will be covered in this course is the basic concept of congruence, complete residue systems, reduced residue systems, Euler's concept, and Euler's theorem. This type of research is quantitative descriptive. Based on the research results, all subjects experienced improvement while implementing the Self-Evaluation Exit Ticket assessment strategy. This increase was seen at meeting 2, namely as many as 55% of students were able to determine their learning outcomes, whereas previously at meeting 1 only 33% of students were able to determine their learning outcomes. Subjects thought that learning implemented using Self-Evaluation Exit Tickets was more fun, interesting, and encouraged subjects to continue learning. This means that the Self-Evaluation Exit Ticket assessment strategy can be effective and possible to apply in online learning.